Developing non–technical ward‐round skills. (15th May 2015) - Harvey, Rachel; Mellanby, Edward; Dearden, Effie; Medjoub, Karima; Edgar, Simon
Summary Background Conducting clinical 'rounds' is one of the most onerous and important duties that every junior doctor is expected to perform. There is evidence that newly qualified doctors are not adequately prepared by their undergraduate experiences for this task. The aim of this study was to analyse the challenges pertaining to non‐technical skills that students would face during ward rounds, and to create a model that facilitates the transition from medical student to doctor. Methods A total of 217 final‐year medical students completed a simulated ward round. Free‐text responses were analysed using template analysis applying an a priori template developed from the literature by the research team. This drew on the generic categories of non‐technical skills suggested by Flin et al. Results Ninety‐seven per cent of students agreed or strongly agreed that the simulated ward round improved their insight into the challenges of ward rounds and their perceived ability to work efficiently as an active member of the ward round. The responding students (206) submitted written feedback describing the learning that they planned to use: 800 learning points were recorded, and all could be categorised into one of seven non‐technical skills. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Conducting clinical 'rounds' is one of the most onerous and important duties that every junior doctor is expected to perform </boxed-text> Discussion We believe that improved task efficiency and insight into the challenges of the ward round gained by medical students will lead to an enhancement in performance during clinical rounds, and will have a positive impact on patient safety. We would suggest that undergraduate medical schools consider this model in the preparation for the clinical practice element of the curriculum.